The Southern-Most Ivy: Princeton University from Jim Crow Admissions to Apartheid, 1794-1969 - Bradley, Stefan M. (American Studies, 2017)
This essay reveals the invasiveness of the Civil Rights and Black Power movements. Even a powerful and exclusive Ivy League institution like Princeton University, could not resist the tide of change that arrested the school’s de facto segregation policies. Once black students were officially admitted (after WWII), they led the charge to change the university’s admission policies, curriculum, and investment policies. By demonstrating against their school’s relationship to apartheid South Africa, Princeton’s black students preceded the national anti-apartheid movement by nearly two decades. The efforts of the students to change their school launched Princeton University into a new era of progressivism.